Dinamika Peradilan Islam Pada Masa Kerajaan Turki - Khaerunnisa Karunia; Lomba Sultan; Fatmawati f (Madani: Jurnal Ilmiah Multidisiplin, 2023)
One of the studies in the field of law and justice is the historical aspect which experts usually call At-Tarikh T-Tasyri' al-Islami. In their study, the researchers selected the history of the development of Islamic law in certain periods. Islamic law during the Ottoman Empire belonged to the last six periods, namely the taqlid period. What is meant by the taqlid period is a period which, among other things, is marked by the tendency of the ulama to provide adequate coverage of the Islamic community to books inherited from previous periods.